2012
DOI: 10.1108/13664381211211046
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation as a determinant of house price

Abstract: Purpose -Tobler's law of geography states that things that are close to one another tend to be more alike than things that are far apart. In this regard, the spatial pattern of price distribution is defined by the arrangement of individual entities in space and the geographic relationships among them. The purpose of this paper is to provide emerging findings of research analysing the salient factors which impact on the sale price of residential properties using a spatial regression approach. Design/methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…Several hedonic studies emphasize the appealing empirical performance of GWR. As expected, Saefuddin and Yekti (2012), Hanink et al (2012) and McCord et al (2012) reported a better GWR performance compared to OLS. Kestens et al (2006) and Bitter et al (2007) measured GWR against the spatial expansion model, and verified that the GWR model outperforms the spatial expansion model in terms of explanatory power and predictive accuracy.…”
Section: Geographically Weighted Regression Modelsupporting
confidence: 79%
“…Several hedonic studies emphasize the appealing empirical performance of GWR. As expected, Saefuddin and Yekti (2012), Hanink et al (2012) and McCord et al (2012) reported a better GWR performance compared to OLS. Kestens et al (2006) and Bitter et al (2007) measured GWR against the spatial expansion model, and verified that the GWR model outperforms the spatial expansion model in terms of explanatory power and predictive accuracy.…”
Section: Geographically Weighted Regression Modelsupporting
confidence: 79%
“…In interesting paper of [26] a GWR model is established to explore spatially varying relationships between house price and floor area with sampled house prices in London. It can be stated that in recent years, there has been an increasing interest in the application of geographically weighted regression on housing market for example in research of [27][28][29][30][31].…”
Section: Theoretical Basic Of Conducted Researchmentioning
confidence: 99%
“…Prices and values of real estate depend on many exogenous and endogenous elements, which should be taken into account in the market analysis, with a particular emphasis on detailed location [25][26][27][28]. One of the essential elements of such an analysis is to isolate the impact of location factors that constitute the essence of cartographic reflection of value [29]. Considerations on location in the context of determining the determinants of apartment prices are presented, among others, by Kiel and Zabel [30] and Kolbe et al [31], indicating at the same time relatively simple methods of econometric modelling as a primary tool for identifying location factors.…”
Section: Literature Reviewmentioning
confidence: 99%